A simple score for early risk stratification in acute heart failure. (1st March 2017) - Xanthopoulos, A.; Giamouzis, G.; Tryposkiadis, K.; Paraskevopoulou, E.; Paraskevopoulou, P.; Karagiannis, G.; Patsilinakos, S.; Parissis, J.; Farmakis, D.; Butler, J.; Skoularigis, J.; Triposkiadis, F.
Abstract: Introduction: The use of many acute heart failure (AHF) risk scores is cumbersome. We therefore developed a simple AHF risk score (AHFRS) for early risk stratification. Methods: The study consisted of a prospective derivation cohort (PDC; N = 104; age, 77[21] years; LVEF (%), 35[29]) and a retrospective validation cohort (RVC; N = 141; age, 76[15] years; LVEF (%), 35[25]). Clinical, echocardiography and laboratory assessment was performed at admission. The study end-point was death from any cause or HF-rehospitalization at 1 year. Results: In the PDC 46 (44.2%) patients experienced the end-point. Independent prognostic factors of outcome were hypertension (HTN) history, myocardial infarction (MI) history, and admission red cell distribution width (RDW). Multivariate logistic regression indicated 8-, 4-, and 3-times higher odds ratio for development of study end-point in patients without a HTN history, with MI history, and RDW ≥ 15% (median) respectively. Thus in AHFRS, 2 points were assigned for absence of HTN history, 1 point for presence of MI history, and 1 point for RDW values ≥ 15% (0 best possible, whereas 4 worst possible score). The AHFRS identified patients who developed the end-point in the PDC with an area under the ROC curve (AUC) of 0.80 [95% C.I.: (0.71, 0.87)] denoting a high discriminative ability. These findings were confirmed in the RVC, in which the endpoint occurred in 52 (36.9%) patients and the AUC for the AHFRS was 0.82 [95% C.I.: (0.73, 0.89)]. Conclusions: AHFRS is easily obtained at admission and accurately risk stratifies AHF patients.